2019
DOI: 10.3390/ma12142312
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Eutectic Fe-Si-B Alloy as a Phase Change Material in Thermal Energy Storage Systems

Abstract: Fe-26.38Si-9.35B eutectic alloy is proposed as a phase change material (PCM) as it exhibits high latent heat, high thermal conductivity, moderate melting point, and low cost. For successful implementation of it in the latent heat thermal energy storage (LHTES) systems, we investigate the use of graphite as a refractory material that withstands long-term melting/solidification in contact with the Fe-26.38Si-9.35B alloy. The PCM has been thermally cycled up to 1–4 times below and above its melting point at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The suitable refractory materials should meet several requirements: it can be used at high temperatures up to 1300 • C; it should resist molten PCM corrosion after long-term thermal cycles; and it should not pollute molten PCM. Graphite is one of the promising refractory materials that has been investigated by our team [4][5][6][7]10]. With the long-term thermal cycle experiments, we observed that thin carbide layers were formed at the surface, and the penetration of Fe-26Si-9B melt into graphite was insignificant.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The suitable refractory materials should meet several requirements: it can be used at high temperatures up to 1300 • C; it should resist molten PCM corrosion after long-term thermal cycles; and it should not pollute molten PCM. Graphite is one of the promising refractory materials that has been investigated by our team [4][5][6][7]10]. With the long-term thermal cycle experiments, we observed that thin carbide layers were formed at the surface, and the penetration of Fe-26Si-9B melt into graphite was insignificant.…”
Section: Introductionmentioning
confidence: 93%
“…With the third element of Fe added to Si-B-based alloys, a new eutectic Fe-26Si-9B alloy was formed. In the report on the experimental results and theoretical calculations [4], the volume change was measured to be about −2.4% at its melting point of 1223 • C. The heat of fusion was calculated to be 1250 kWh/m 3 , which is a bit higher than that of pure Si. The thermal conductivity was estimated to be 30.6 W/(m•K) at 1100 • C, which is higher than those of most of the organic and inorganic PCMs [16,17].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They are all essential materials for LHS-TES because they have been known to store up to between 5 and 14 times more heat per unit volume than SSMs such as water, masonry or rocks [23]. The determination of whether a PCM is suitable for each application is dependent on the range of temperature such material can handle [24]. Many TES applications use PCM as they are found suitable for their versatile thermal performance [25].…”
Section: Figure 3 Types Of Pcm For Tes [19] [20]mentioning
confidence: 99%
“…Eutectic mixtures have wide industrial importance in many fields including alloys, electronics, refrigeration industry, energy storage, greenhouse gas emission reduction, and chemicals purification. Traditional eutectics in the refrigeration industry are inorganic materials (mixtures of salts) known for a long time. A historical application is related to handmade ice cream, whose more ancient citation is probably back in the fourth century A.D. as reported in the Indian poem Pancatantra .…”
Section: Introductionmentioning
confidence: 99%